Genetic Diversity and Sequence Variations at Growth Hormone Loci among Composite and Hereford Populations of Beef Cattle - SUTARNO SUTARNO; A. J. LYMBERY (Biodiversitas Journal of Biological Diversity, 2000)
A total of 194 Hereford and 235 composite breed cattle from Wokalup Research Station were used in this study. The aims of the study were to: Investigate polymorphisms in the growth hormone gene in the composite and purebred Hereford herds from the Wokalup selection experiment, compare genetic diversity in the growth hormone gene of the breeds, sequencing and compare the sequences of growth hormone loci between composite and purebred Hereford herds with published sequence from Genebank. The genomic DNA was extracted using Wizard genomic DNA purification system from Promega. Two fragments of growth hormone gene were amplified using PCR and continued with RFLP. Each genotype in both loci was sequenced. PCR products of each genotypes were cloned into PCR II, transformed, colonies selection, plasmid DNA extraction continued with cycle sequencing. Polymorphisms were found in both breeds of cattle in both loci of GH-L1 and GH-L2 of the growth hormone gene by PCR-RFLP analysis. Sequencing analysis confirmed the RFLPs data, polymorphism detected using AluI at GH-L1 is due to substitution between leusin/ valine at position 127, while polymorphism at the MspI restriction site was caused by transition of C to T at +837 position.Â© 2000 Jurusan Biologi FMIPA UNS SurakartaKey words: PCR-RFLP, sequencing, growth hormone gene, polymorphism